Bilateral epidermal nevi in the external auditory canals treated with CO2 laser. Issue 2 (10th January 2020) - Rajpal, Neha; Dilorenzo, Ashley; Parsa, Keon; Hoa, Michael; Ronkainen, Sanna
Abstract: Epidermal nevi are benign hamartomas of the epidermis and adnexal structures of the skin. We present the case of epidermal nevi in the bilateral external auditory ear canals of an otherwise healthy 23‐year‐old woman treated with CO2 laser ablation.